2022
DOI: 10.33200/ijcer.800990
|View full text |Cite
|
Sign up to set email alerts
|

The Pandemic Period and the Parent-Child Relationship

Abstract: This article may be used for research, teaching, and private study purposes.Any substantial or systematic reproduction, redistribution, reselling, loan, sub-licensing, systematic supply, or distribution in any form to anyone is expressly forbidden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 67 publications
4
11
0
1
Order By: Relevance
“…However, some families reported positive experiences such as finding new hobbies and developing positive characteristics such as appreciation, gratitude, and tolerance. A similar study conducted by Ongören (2021) examining family relationships showed a positive result. Participants mostly gave upbeat assessments of relationships within the family during the pandemic, stating they were together, supported each other, and established positive communication.…”
Section: Floaters: What Pulls Us Afloatmentioning
confidence: 63%
See 1 more Smart Citation
“…However, some families reported positive experiences such as finding new hobbies and developing positive characteristics such as appreciation, gratitude, and tolerance. A similar study conducted by Ongören (2021) examining family relationships showed a positive result. Participants mostly gave upbeat assessments of relationships within the family during the pandemic, stating they were together, supported each other, and established positive communication.…”
Section: Floaters: What Pulls Us Afloatmentioning
confidence: 63%
“…Participants mostly gave upbeat assessments of relationships within the family during the pandemic, stating they were together, supported each other, and established positive communication. Concluding further by the author that this situation shows that individuals preserve the importance of the concept of family and that even if conditions change, they continue to pay attention to relationships within the family (Ongören, 2021).…”
Section: Floaters: What Pulls Us Afloatmentioning
confidence: 95%
“…Anneler son 1 yılı göz önünde bulundurarak (salgın başladığından bu yana) çocukları ile iletişim düzeylerini orta düzey olarak değerlendirmektedir. Bu bulgu sosyal izolasyonun getirdiği psikolojik etkilerin aile ilişkilerine yansımasına yönelik çalışmaları destekler niteliktedir (Liu ve Doan 2020, Öngören 2021. Ebeveynle çocuk arasındaki iletişimin COVID-19 sürecinden nasıl etkilendiğini inceleyen başka bir çalışmada annebabaların çocukla iletişiminde konuşma ve dinleme boyutlarında pandemiden olumsuz etkilendiği ortaya çıkmıştır (Döğer ve Kılınç 2021).…”
Section: Discussionunclassified
“…The paradoxical online learning experience of parents and children during the pandemic is a subjective psychological process in which each individual has a unique perspective on the same object or event (Dong et al, 2020;Qiong, 2017). These distinctions may influence their relationship and result in conflict ( Öngören, 2021;Eyimaya & Irmak, 2021) or maltreatment of children (Griffith, 2020;Rodriguez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%